2002
DOI: 10.1309/mur1-05a4-184q-qctr
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Latex Agglutination With Enzyme Immunoassay for Detection of Rotavirus in Fecal Specimens

Abstract: Human rotaviruses are the most important etiologic agents of acquired diarrhea in infants and young children worldwide. Early diagnosis is essentialfor effective patient treatment. The latex agglutination (LA) assays for rotavirus diagnosis are rapid, inexpensive, and the most widely used to screen specimens. The performance of the LA Rotagen (Biokit S.A., Barcelona, Spain) was evaluated for rotavirus detection infecal samples of outpatients with acute gastroenteritis. This assay was compared with the enzyme i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…Although this technique may be useful in certain situations, such as outbreaks of the disease, or in locations with lack of resources for RV detection, because it is fast, practical and has low cost. 31,50 A different distribution of positive samples was observed using this method in different years, with a progressive decline in the number of samples investigated since 2004. A study to assess the impact of vaccination against rotavirus has been previously conducted by our institution.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although this technique may be useful in certain situations, such as outbreaks of the disease, or in locations with lack of resources for RV detection, because it is fast, practical and has low cost. 31,50 A different distribution of positive samples was observed using this method in different years, with a progressive decline in the number of samples investigated since 2004. A study to assess the impact of vaccination against rotavirus has been previously conducted by our institution.…”
Section: Discussionmentioning
confidence: 94%
“…19,[26][27][28][29][30][31] Currently, several commercial tests are available from those based on less laborious techniques that enable a quick diagnosis, e.g. antigen detection methods, to more complex tests such as the polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several decades after the rotavirus description many studies have been carried out to compare detection techniques (11,(16)(17)(18)(19)(20)(21) . Currently, several commercial tests are available from less laborious based techniques that enable a quick diagnosis, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Raboni SM et al and Bahl R et al supported this observation of the present study. They reported that the majority of the cases of rotavirus diarrhea occurred in children younger than 2 years [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Swab swirled ten times until the sample was dissolved into the assay diluents and swab was discarded while squeezing the swab against the wall of tube. [10][11][12][13][14][15][16][17][18][19][20] minutes.…”
Section: Assay Diluent Was Taken In a Disposablementioning
confidence: 99%